EVALUATION OF THE FLU SYNDROME SENTINEL SYSTEM IN FORTALEZA – CE - Hil´ario Magalhães , Poliana; Silva da Cunha , Ludmila; Neto Goes da Silva , Isaac; Marinho Campelo, Cassio (Cadernos ESP, 2025)
Objective: Evaluating the Influenza Syndrome Surveillance System in the Fortaleza city – Ceará state, from 2021 to 2023. Method: Epidemiological study on the Influenza Syndrome Sentinel Surveillance System based on a descriptive study with a retrospective approach considering the CDC guidelines for assessing data quality and representativeness. Results: Data analysis showed variations in sample collection in sentinel units, with unsatisfactory performance and a drop in targets from 2022 onwards. Data quality and consistency were classified ‘Excellent’. Fortaleza obtained a satisfactory classification in terms of the proportion of sentinel units. Teams must be continuously trained to ensure quality in respiratory virus surveillance. Conclusion: Sentinel surveillance is essential for monitoring respiratory diseases and identifying circulating viruses, and its success depends on improving data quality and the representativeness of sentinel units.
Keywords: Sentinel surveillance; Respiratory tract disease; CDC